Chrťien de Troyes : an analytic bibliography. - Kelly, Douglas (Research bibliographies & checklists. New series, 2002)
The Supplement builds on the original Chrétien de Troyes Bibliography; together the two volumes constitute the fullest and most complete bibliographical source now available on this major medieval author. The bibliography lists recent Chrétien scholarship under twenty-two topics, with numerous sub-sections under each topic, and cross-references for items that treat more than one of the topics. The scope of modern Chrétien studies is evident in items from the five continents.